Public open spaces and physical activity: disparities of resources in Florianópolis - Sofia Wolker Manta; Rodrigo Siqueira Reis; Tânia Rosane Bertoldo Benedetti; Cassiano Ricardo Rech (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To analyze the association between sociodemographic characteristics of census tracts and the presence/quality of public open spaces and physical activity facilities. METHODS: A cross-sectional study was conducted in 643 census tracts in Florianópolis, Brazil, the presence and quality of public open spaces and physical activity facilities were objectively analyzed and the data by census tracts using Geographic Information Systems was treated. Outcomes were analyzed considering the census tracts as having: ≥ 1 public open spaces; ≥ 1 public open spaces with high quality; ≥ 2 physical activity facilities and high-quality physical activity facilities. Sociodemographic characteristics were the independent variables. Logistic regression analysis was performed. RESULTS: Census tracts with a medium-income (OR = 1.8; 95%CI 1.1-3.0) and high-income (OR = 2.4; 95%CI 1.4-4.0), in those with medium (OR = 1.7; 95%CI 1.0-2.7) and high residential density (OR = 2.0; 95%CI 1,2-3.3), and with higher proportions of older adults (OR = 3.3; 95%CI 1.9-5.7) had a higher proportion of public open spaces. Census tracts with higher proportions of children/adolescents (OR = 0.3; 95%CI 0.2-0.6) and non-white residents (OR= 0.6; 95%CI 0.3-0.9) were less likely to contain public open spaces. The tracts with medium (OR = 4.0; 95%CI 1.4-11.3) and high-income (OR = 3.6; 95%CI 1.2-10.2) were more likely to contain public open spaces with ≥ 2 structures for physical activity, compared with those with low-income. We observed the inverse in sectors with a high proportion of non-white residents (OR = 0.3; 95%CI 0.1-0.9). CONCLUSIONS: Census tracts with higher proportions of children or adolescents, non-white individuals and those in the low-income strata had lower odds of containing public open spaces and physical activity facilities.